Pelatihan dasar-dasar robotik di Sekolah Kreatif SD Muhammadiyah 19 Rogojampi untuk meningkatkan kreativitas siswa serta pemahaman robotika - Yuliandoko, Herman; Kusuma, Dedy Hidayat; Pamuji, Dian Ridlo; Shodiq, Moh. Nur (Cahaya Pengabdian, 2024)
Analog-based robotic training is one of the educational innovations that improves students' creativity and critical thinking skills. This activity aims to describe the implementation of analog line follower robotic training at the Creative School of Muhammadiyah Elementary School 19 Rogojampi as an effort to foster students' creativity, interest, and skills in technology. The method used is descriptive with a participatory approach, involving grade VI students as participants. This training begins with a theory of introducing the basics of robotics and its supporting electronic components, followed by the practice of assembling a simple analog line follower robot. The results of the training showed that students were able to understand the basic concepts of robotics and succeeded in making a robot that could follow the path independently. In addition, this activity also increased students' creativity through technology. Analog Line Follower robotic training at the Creative School of Muhammadiyah Elementary School 19 Rogojampi has a positive impact on fostering students' interest in technology and building 21st-century skills such as collaboration and innovation. Similar programs are recommended to be implemented in other schools to support STEM (Science, Technology, Engineering, and Mathematics)-based learning. Keywords: creative, student, robotic, line follower, assembly